Psychometric properties of concussion knowledge and cognitive mediators of reporting measures. (24th August 2021) - McCarthy, Kevin S.; Kneavel, Meredith; Ernst, William
ABSTRACT: Context : Concussion education and prevention programs require reliable and valid instruments to evaluate the theory, mechanisms, and outcome of these interventions Objective : To assess the psychometric properties of measures evaluating concussion education and prevention programsDesign : Descriptive epidemiological Setting: 10 NCAA-member universities Patients or Other Participants : 841 student-athletes in an RCT control group testing an ecological, peer-led concussion education program Main Outcome Measures : Instruments adapted for assessing concussion knowledge and Theory of Planned Behavior/Theory of Reasoned Action (TPB/TRA) cognitive mediators of reporting behavior (attitudes, subjective norms, perceived control, and intentions to report concussion). Participants completed measures at baseline, after one hour, and after one month Results : Internal consistency and test-retest reliability were moderate for both the concussion knowledge and cognitive mediator measures. TPB/TRA was supported subscale intercorrelation and item factor analysis in the cognitive mediator scale. Factor analysis of the concussion knowledge measure revealed subscales for physical/cognitive, psychological/affective, and non-symptoms. The intermediate TPB/TRA mediators of attitudes, norms, and perceived control predicted greater intention-to-report, which predicted increased likelihood of reporting concussion one month later.Conclusions : Measures of concussion knowledge and cognitive mediators of reporting adapted from the literature show adequate psychometric properties and support TPB/TRA application for concussion reporting behaviors.